2019
DOI: 10.1186/s12889-019-6863-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice towards sexually transmitted diseases amongst the inmates of women shelters homes at Klang Valley

Abstract: Background Previous studies show that there is a changing trend of sexual and reproductive behaviour among youth and this requires more attention and awareness especially on sexually transmitted diseases (STD). This study was carried out to evaluate the knowledge, attitude and practice of sexually transmitted diseases among selected inmates of women shelter homes. Methods A cross-sectional study was carried out by involving 60 participants whom aged in between 13 to 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 22 publications
5
15
1
1
Order By: Relevance
“…This finding was higher than 27% in Udupi Taluk, India [ 25 ]. However, lower than 45.4% in Gondar, Ethiopia [ 35 ], 68.3% in the Klang Valley, Malaysia [ 24 ], 70.1% in northern Cape Province, South Africa [ 26 ], 74.7% in urban slums of Jorhat District, India [ 15 ], 79% in Dhaka, Bangladesh [ 20 ], 86.6% in Malaysia [ 21 ], 89.9% in Brazil [ 17 ], 92.4% in Nigeria [ 16 ], and 98% in Dar es Salaam, Tanzania [ 18 ]. The variation observed compared to other studies could be due to the differences in methodology, sample size, and operational definition used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was higher than 27% in Udupi Taluk, India [ 25 ]. However, lower than 45.4% in Gondar, Ethiopia [ 35 ], 68.3% in the Klang Valley, Malaysia [ 24 ], 70.1% in northern Cape Province, South Africa [ 26 ], 74.7% in urban slums of Jorhat District, India [ 15 ], 79% in Dhaka, Bangladesh [ 20 ], 86.6% in Malaysia [ 21 ], 89.9% in Brazil [ 17 ], 92.4% in Nigeria [ 16 ], and 98% in Dar es Salaam, Tanzania [ 18 ]. The variation observed compared to other studies could be due to the differences in methodology, sample size, and operational definition used.…”
Section: Discussionmentioning
confidence: 99%
“…The health-seeking behavior of STIs may largely depend on knowledge about STIs [ 14 ]. Several studies have been conducted worldwide regarding knowledge about STIs and reported that 74.7% in India [ 15 ], 92.4% in Nigeria [ 16 ], 89.9% in Brazil [ 17 ], 98% in Tanzania [ 18 ], 88.5% in Jimma, Ethiopia [ 19 ], 79% in Dhaka, Bangladesh [ 20 ], 86.6% in Malaysia [ 21 ], 74% medical and 61.6% non-medical university students in Pakistan [ 22 ], 83.1% in Turkey [ 23 ], 68.3% in Klang Valley, Malaysia [ 24 ], 27% in Udupi Taluk, India [ 25 ], and 70.1% in northern Cape Province, South Africa [ 26 ] of the respondents had good knowledge of STIs. The factors that influence knowledge of STIs are diverse and include age, sex, residence, marital status, academic year, and acquiring information from friends/internet and mass media [ 5 , 18 , 27 - 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although, majority of the students in this study correctly identified that monogamy (82.0%) helps to reduce the risk of STDs infection, surprisingly, half of the students who were sexually active for the past 12 months, had sex with more than one partner. Likewise, a study at Klang Valley revealed that despite having immense knowledge of preventive practices, more than half of the participants admitted having three or more sexual partner 16 . Thereby, having complete understanding on its own does not always guarantee the behaviour and practice of a person.…”
Section: Table 4: Associations Of Knowledge and Preventive Practices mentioning
confidence: 99%
“…Zin's research (2019) states that knowledge of STIs is very important to reduce STI transmission. The high prevalence of STIs such as HIV, gonorrhea, and syphilis one of the risk factors is knowledge [17]. To increase the knowledge of STI, it can be done through various ways, namely through health promotion from the internet, television, radio.…”
Section: B Knowledge Images Of Students Senior High School (Sman) 2 mentioning
confidence: 99%